Early bubble continuous positive airway pressure as the initial mode of management of respiratory distress syndrome in preterm neonates - Tahreem, Nazish; Malagi, Naushad N.; Thobbi, A. N.; Raziyabanu (International Journal of Contemporary Pediatrics, 2025)
Background: Respiratory distress syndrome (RDS) is a common and serious condition in preterm neonates caused primarily by surfactant deficiency and immature lungs. Early application of bubble continuous positive airway pressure (bCPAP) offers a non-invasive respiratory support method that may reduce the need for mechanical ventilation and associated complications. The present study aimed to evaluate the efficacy and safety of early bubble CPAP as the initial mode of respiratory support in preterm neonates with RDS. Methods: A prospective observational study was conducted on 100 preterm neonates between 28 and 34 weeks of gestation presenting with clinical and radiological features of RDS within 6 hours of birth. All neonates were initiated on bCPAP within 1 hour of birth or diagnosis. The primary outcome was bCPAP success, defined as avoidance of invasive mechanical ventilation within 72 hours. Secondary outcomes included the duration of bCPAP therapy, complications, incidence of bronchopulmonary dysplasia (BPD), length of stay in the neonatal intensive care unit (NICU), and survival to discharge. Results: The mean gestational age and birth weight were 31.5±1.8 weeks and 1450±320 grams, respectively. Successful bCPAP therapy was achieved in 72% of neonates. The mean duration of bCPAP was 72.12±18.54 hours. Complications included apnea requiring intubation (12%), nasal trauma (10%), pneumothorax (5%), and BPD (8%). Neonates who failed bCPAP had significantly lower gestational ages and birth weights and higher incidences of BPD and mortality (p<0.05). Survival to discharge was 94%. Conclusion: Early bubble CPAP is an effective and safe respiratory support strategy in preterm neonates with RDS, reducing the need for mechanical ventilation and associated complications.